Problems with the Legal Status of Land Ownership Anak Dalam Tribe Indigenous People - Reni Fatmala Sari; Sapto Hermawan; Andina Elok Puri Maharani (Faculty of Law, Universitas Pekalongan, 2023)
This study aims to examine and analyze the legal status of land ownership for the indigenous people of the Suku Anak Dalam in Batanghari Regency, as well as the legal status of land ownership for the indigenous people of the Suku Anak Dalam in Batanghari Regency. This research will be conducted by looking at the positive and negative aspects of land ownership. In this technique, the author's legal research is used as the main emphasis (legal research). The results of the study show that the existence of regulation P.6/KSDAE/SET/Kum.1/6/2018 has not accommodated the intent of Law Number 5 of 1990 concerning Conservation Article 32 and Law Number 41 of 1999, which state that national park areas are managed with a zoning system consisting of core zones, utilization zones, and other zones according to requirements. This regulation indicates that other zones within a national park, such as rehabilitation zones, special zones, and religious, cultural, and historical zones, are allowed to be managed in accordance with the mandate, while Perdirjen P.6/KSDAE This condition will certainly lead to multiple interpretations of access zoning management by related parties, including the village government and the local community.